David Burliuk in Color and Rhyme Magazine. Article 1. Painter and Poet on the Crossroads of Cultures - Anna A. Arustamova (Литература двух Америк, 2021)
The paper traces David Burliuk’s evolution as a poet, essayist and editor in the United States, where he began his career in the pro-Soviet Russian émigré newspaper Russky Golos and then switched to his personal project — Color and Rhyme, the Burliuk family magazine. The paper examines some strategies of Burliuk's self-presentation in Color and Rhyme; since in this edition Burliuk is presented as a poet and an artist, the paper analyzes, how both of these roles of Burliuk relate to each other in the texts published in the magazine. Focusing on the English-speaking reader, Burliuk emphasized the European context of his artistic biography; other contributors that published their articles and reviews in the Color and Rhyme stressed his cultural affinity with Paul Gaugin, Expressionists, Fauvists and characterized Burliuk as “American Van Gogh”. Special attention is paid to the ways of representation of American poetry in Color and Rhyme. Burliuk’s magazine published works by members of some New York poetic communities, such as The New York Poetry Forum and The Raven Poetry Circle of Greenwich Village. In particular, it is described how Burliuk as an editor represented beginners or littleknown authors in the earlier periods of his editorial activity. The article shows that Color and Rhyme magazine can be viewed not only as a tool for “promoting” D. Burliuk's art, but also as a chronicle of his activity as a writer and artist.